An Injectable Hydrogel for Enhanced FeGA-Based Chemodynamic Therapy by Increasing Intracellular Acidity - Zeng, Wen; Jiang, Dazhen; Liu, Zeming; Suo, Weilong; Wang, Ziqi; Zhu, Daoming; Huang, Qinqin (Frontiers in Oncology, 2021)
Hydroxyl radical (•OH)-mediated chemodynamic therapy (CDT) is an emerging antitumor strategy, however, acid deficiency in the tumor microenvironment (TME) hampers its efficacy. In this study, a new injectable hydrogel was developed as an acid-enhanced CDT system (AES) for improving tumor therapy. The AES contains iron–gallic acid nanoparticles (FeGA) and α-cyano-4-hydroxycinnamic acid (α-CHCA). FeGA converts near-infrared laser into heat, which results in agarose degradation and consequent α-CHCA release. Then, as a monocarboxylic acid transporter inhibitor, α-CHCA can raise the acidity in TME, thus contributing to an increase in ·OH-production in FeGA-based CDT. This approach was found effective for killing tumor cells both in vitro and in vivo, demonstrating good therapeutic efficacy. In vivo investigations also revealed that AES had outstanding biocompatibility and stability. This is the first study to improve FeGA-based CDT by increasing intracellular acidity. The AES system developed here opens new opportunities for effective tumor treatment.